Analisis Penerapan Lean Learning Pada Pembelajaran Pendidikan Vokasi With Literature Review Analysis - Gofur, Muhamad; Hasibuan, Sawarni; Purba, Humiras Hardi (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
Based on an estimate for 2030, Indonesia's workforce needs are estimated to reach 113,000,000 people. From data from the Central Statistics Agency (BPS) the Open Unemployment Rate (TPT) in Indonesia reached 8.42 million people as of August 2022. The highest TPT, namely 9.42%, was contributed by SMK graduates. Seeing this, an action is needed to align learning in the classroom to suit the needs of the industrial world. The literature review approach is used to find research gaps in the application of lean learning in vocational education using VosViewers. Based on the results of the VosViewers analysis and the SOTA matrix, it was found that the use of SERVQUAL has been quite widely applied in the service sector, but the combination of EDUQUAL and KANO has not been widely studied in the education world, especially in LEAN LEARNING research in vocational education.